Mining-Induced Stress and Ground Pressure Behavior Characteristics in Mining a Thick Coal Seam With Hard Roofs - Zhu, Zhijie; Wu, Yunlong; Liang, Zhuang (Frontiers in Earth Science, 2022)
The hard roof of coal mine has the characteristics of high hardness, good integrity and large layer thickness, which leads to many ground control problems. To reveal the influence of hard roof structure on the stress performance and coal pillar stability during mining operations, the 8104 and 8105 working faces in Tongxin Coal Mine was taken as the research object to analyze the stress behavior during the working face advance. Numerical simulation software FLAC3D was used to establish the numerical model of longwall face under hard roof conditions. The stress distribution laws and coal pillar stability under different roof strengths were analyzed so as to explain the impacts of the hard roof on the stress distribution at the working face. The results shows that during the second face proceeding, the influence zone of the front abutment pressure under hard roof conditions is 6 m wider than that under soft roof conditions, and the bearing stress at the working face is 10.4 MPa higher. At the mining position, the plastic zone of the pillar under hard roof conditions is 11 m wider than that under soft roof conditions, and the peak vertical stress is hinger 5.13 MPa than that under soft roof conditions. At 25 m ahead of the working face, the plastic zone of the pillar under hard roof conditions is 6 m wider than that under soft roof conditions, and the peak vertical stress is hinger 24.84 MPa than that under soft roof conditions. Additional overburden pressure produced by uncaved hard roof increased pillar stress and plastic zones. Therefore, hard roof is main cause of strong ground pressure behavior in Tongxin Coal mine. Aiming at the strong mine pressure behavior , it is suggested to adopt pre-splitting technology to reduce the influence of the hard roof on mine pressure.